Pengaruh Pemberian Pendidikan Kesehatan tentang Perkembangan Penyakit Pasien terhadap Tingkat Kecemasan Keluarga Yang Dirawat di Ruang ICU RS Ananda Bekasi - Futriani, Elfira Sri; Muzdalivah, Silvia (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Health education is a learning strategy aimed at motivating the public to adopt practices that support their health. This process provides individuals with opportunities to enhance their health literacy and practical skills in self-health management (Putri et al., 2018). The WHO 2021 report indicates an annual increase in the prevalence of critical patients in ICUs, with 9.8-24.6 per 100,000 people experiencing comas. Globally, deaths from serious illnesses range from 1.1 to 7.4 million per year. Purpose: To understand and analyze the Impact of Providing Health Education on the Progress of Patient Diseases on the Anxiety Levels of Families Cared for in the ICU of Ananda Bekasi Hospital in 2024. The method in this study is analytic with a quasi-experimental approach. The sample in this study included all family members of patients cared for in the ICU of Ananda Bekasi Hospital, totaling 49 people, with total sampling technique used for sample collection. There is an impact of Providing Health Education on the Development of Disease on the Anxiety Levels of Families of patients in the ICU of Ananda Bekasi Hospital with a p-value of 0.000. Conclusion: Health education is effective in reducing the anxiety of ICU patient families, with significant statistical evidence (p-value 0.000). This strategy enhances the family's understanding of medical conditions and strengthens their sense of control over the situation. Keywords: Health Education Provision, Anxiety Level, ICU Room.  ABSTRAK Pendidikan kesehatan adalah strategi pembelajaran yang bertujuan memotivasi masyarakat untuk mengadopsi praktik yang mendukung kesehatan. Proses ini menyediakan kesempatan bagi individu untuk meningkatkan literasi dan kemampuan praktis mereka dalam mendukung kesehatan diri (Putri et al., 2018). Laporan WHO 2021 menunjukkan peningkatan tahunan prevalensi pasien kritis di ICU, dengan 9,8-24,6 per 100.000 orang yang mengalami koma. Global, kematian karena penyakit serius mencapai 1,1-7,4 juta per tahun. Mengetahui dan menganalisis Pengaruh Pemberian Pendidikan Kesehatan Tentang Perkembangan Penyakit Pasien Terhadap Tingkat Kecemasan Keluarga Yang Dirawat di Ruang ICU RS Ananda Bekasi Tahun 2024. Metode pada penelitian ini adalah analitik dengan pendekatan quasy eksperimental. Sampel dalam penelitian ini adalah seluruh Keluaga paisen yang dirawat di ruang ICU RS Ananda Bekasi sebanyak 49 orang, dengan teknik pengambilan sampel total sampling. Terdapat pengaruh Pemberian Pendidikan Kesehatan Tentang Perkembangan Penyakit terhadap tingkat Kecemasan Keluarga pasien yang dirawat di Ruang ICU RS Ananda Bekasi dengan nilai p-value 0.000. Pendidikan kesehatan efektif dalam mengurangi kecemasan keluarga pasien ICU, dengan bukti statistik signifikan (p-value 0.000). Strategi ini meningkatkan pemahaman keluarga tentang kondisi medis dan memperkuat rasa kontrol mereka atas situasi. Kata Kunci: Pemberian Pendidikan Kesehatan, Tingkat Kecemasan, Ruang ICU.